2016
DOI: 10.1111/pim.12332
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica induces human neutrophils to form NETs

Abstract: Entamoeba histolytica invades the intestine and other organs during the pathogenesis of amoebiasis. In the early stages, the host organism responds with an inflammatory infiltrate composed mostly of neutrophils. It has been reported that these immune cells, activated by E. histolytica, exert a protective role by releasing proteolytic enzymes and generating reactive oxygen/nitrogen species (ROS/RNS) and antimicrobial peptides. It is now known that neutrophils also produce neutrophil extracellular traps (NETs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…A high percentage of immature neutrophils increases host susceptibility to secondary infections (Cunnington et al, 2012). Moreover, parasites from mastigophora, sarcodina and sporozoa phyla as well as helminths have been shown to trigger NET formation in vivo and/or in vitro (Baker et al, 2008; Abi Abdallah et al, 2012; Rochael et al, 2015; Ventura-Juarez et al, 2016). Although there seems to be an agreement that these structures trap microbes (Hermosilla et al, 2014), data that bear on the ability of NETs to kill parasites is at variance (Guimaraes-Costa et al, 2009; Hermosilla et al, 2014; McCoy et al, 2017).…”
Section: Parasitesmentioning
confidence: 99%
“…A high percentage of immature neutrophils increases host susceptibility to secondary infections (Cunnington et al, 2012). Moreover, parasites from mastigophora, sarcodina and sporozoa phyla as well as helminths have been shown to trigger NET formation in vivo and/or in vitro (Baker et al, 2008; Abi Abdallah et al, 2012; Rochael et al, 2015; Ventura-Juarez et al, 2016). Although there seems to be an agreement that these structures trap microbes (Hermosilla et al, 2014), data that bear on the ability of NETs to kill parasites is at variance (Guimaraes-Costa et al, 2009; Hermosilla et al, 2014; McCoy et al, 2017).…”
Section: Parasitesmentioning
confidence: 99%
“…By now, NETosis has been described to be triggered by different protozoan parasites in vitro and in vivo , such as Plasmodium falciparum (29), Leishmania spp. (30, 31), Eimeria bovis (12, 32), Eimeria arloingi (33), T. gondii (34, 35), Besnoitia besnoiti (11), Cryptosporidium parvum (13), Trypanosoma cruzii (36), and Entamoeba histolytica (37). In addition, monocyte-derived extracellular traps have recently been reported in response to tachyzoites of B. besnoiti (11) and T. gondii in vitro (35).…”
Section: Introductionmentioning
confidence: 99%
“…Brinkmann and colleagues first described the formation of neutrophil extracellular traps (NETs) in 2004; the focus of the subsequent investigations was the host immune protection carried out by NET fibers. Still, several studies have shown the beneficial effects of NETs against various pathogens such as E. coli, S. aureus, P. aeruginosa, Aspergillus fumigatus, Borrelia burgdoferi, Human immunodeficiency virus, Myxoma virus, C. albicans, Entamoeba histolytica, GBS, GPAC, and T. gondii [22][23][24][25][26][27][28][29][30]. Interestingly, NET formation, instead of phagocytosis-mediated killing, was described to occur depending on the size of the invading pathogen and was named size-selective NETosis [95].…”
Section: Extracellular Traps In Homininaementioning
confidence: 99%